Experience of therapy of chronic viral hepatitis c patients with unfavourable response predictors - N. I. Geyvandova; A. V. Lipov; P. V. Koroy; A. V. Yagoda; S. S. Rogova (Медицинский совет, 2016)
Introduction in practice of therapeutic establishments in the RF of antiviral therapy of chronic viral hepatitis in the form of interferon-free schemes led to considerable increase of the frequency of the stable virologic response. Study objective: determination of virologic response predictors in CVHC patients when various therapeutic schemes are used. Materials and methods: Group 1 of CVHC 52 patients with genotype 1 of HCV received standard anti-viral therapy, Group 2 (21 subject) – interferon-free scheme (Viekira Pak+ Ribavirin). Genetic polymorphisms IL-28В rs12979860 (С>Т) and rs8099917 (Т>G) and blood interferon-γ induced protein – IP-10 were determined. Results: standard anti-viral therapy in Group 1 resulted in SVR (sustained viral response) in 29 patients (55.7%). In Group 2 that received Viekira Pak 100% SVR was achieved in spite of more frequent F3 and 4 stage of fibrosis, unsuccessful anti-viral therapy (9 persons), contraindications to IFN-α drugs (6 persons). Unfavorable genotypes IL-28B ТТ (rs12979860) and GG (rs8099917) were associated in Group 1 with lack of SVR, level of IP-10 in patients with SVR was lower than the one in non-respondents. The therapy by Viekira Pak was well tolerated and resulted in SVR despite presence of grave hepatic fibrosis/ cirrhosis, concomitant pathology, unfavourable options of IL-28B, high IP-10 protein levels. Conclusion: choice of optimal anti-viral therapy schemes for each patient with CVHC must be done taken into account all possible predictors, which allows optimizing the therapy and preventing the necessity of repeated therapy.